2017
DOI: 10.3390/s17030499
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Experimental Performance Evaluation of BLE Neighbor Discovery Process Including Non-Idealities of Real Chipsets

Abstract: The purpose of this paper is to evaluate from a real perspective the performance of Bluetooth Low Energy (BLE) as a technology that enables fast and reliable discovery of a large number of users/devices in a short period of time. The BLE standard specifies a wide range of configurable parameter values that determine the discovery process and need to be set according to the particular application requirements. Many previous works have been addressed to investigate the discovery process through analytical and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 13 publications
(19 reference statements)
0
32
0
Order By: Relevance
“…Nevertheless, the duration of all these "blind times" in this case does not depend on the configured Scan_Window and Scan_Interval parameters. Other devices also present these frequency change gaps (depicted in black) but they also introduce other periodic blind times (depicted in red) associated with unknown processes of the manufacturer firmware implementation [3,19].…”
Section: A Characterization Of the Receiver In Scanning Modementioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, the duration of all these "blind times" in this case does not depend on the configured Scan_Window and Scan_Interval parameters. Other devices also present these frequency change gaps (depicted in black) but they also introduce other periodic blind times (depicted in red) associated with unknown processes of the manufacturer firmware implementation [3,19].…”
Section: A Characterization Of the Receiver In Scanning Modementioning
confidence: 99%
“…They may also be different when the received frame is demodulated correctly or not. More details can be found in [3,19].…”
Section: B Characterization Of the Receiver During Frame Receptionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, analytical and simulation studies do not take into account the non-idealities present in real devices. In [ 13 ], we have shown that these non-idealities have a severe impact on discovery capacity. In this paper, we will focus on a comparative evaluation of scannable undirected vs. non-connectable advertisements to be employed in high density networks to provide the location and transmission of information where a large number of devices are involved.…”
Section: Introductionmentioning
confidence: 99%